Job stress and job performance: A case study of Kuching Court Sarawak / Josephine Thomas - Thomas, Josephine (2018)
Job Stress and Job Performance are closely related to one another. It is a causal and effect relationship. It has been a study of many scholars and the issue contributes to job stress aggravates from time to time. Many may not realize how job stressors influence job performance other than complaining. Job stress can be seen into two parts namely job demands and job resources. The independent variable is job stress consisting job demands and job resources while dependent variable is job performance. This study examines job stress and job performance relationship in one of Judiciary department a case study conducted at Kuching court, Sarawak. The result reveals that there is high level of stress and significant relationship between job stress and job performance in Kuching court, Sarawak. There are significant differences in job performance and length of service also proven from this study. A self-administered questionnaires survey collected data from the sample of case study, employees of Kuching court who are 31 males and 69 females. Nevertheless, this study introduces positive relationship between job stress and job performance. It is the greatest hope that this study can provide an insight and better understanding pertaining to job stress and job stress management in thriving job performance in the future not only in the Judiciary but in public organization in general.